Reproductive Biology of Round Herring Etrumeus teres (Dekay, 1842) from the Egyptian Mediterranean Water at Alexandria. (30th March 2011) - Osman, Alaa G. M.; Akel, El Sayed H.; Farrag, Mahmoud M.; Moustafa, Mohsen A.
Abstract : Maturity stages of round herring Etrumeus teres were divided anatomically into six stages. Monthly distribution of such maturity stages showed that E. teres had prolonged spawning season extended from December to May for females and to July for males. The observed sex ratio was 1 : 2 (male: female). Gonadosomatic index (GSI) values were high during breeding season for both sexes. Hepatosomatic index (HIS) values for females increased from December to April and from December to July for males. Both sexes of E. teres showed the same correlation between GSI and HSI during their breeding season. The absolute and relative fecundity increased with increasing of length and weight. Histologically, the ovarian cycle of E. teres was classified into six stages and the testicular cycle into five stages. Female of E. teres was a multiple spawner and had prolonged spawning season with a group-synchronous ovarian which contained oocytes at all stages of development. Also, different sizes of spermatocytes at different developmental stages of maturation were observed during the same season. This may reflect the suitability of the specific reproductive behavior of male and its adaptation to the prolonged spawning season with females.